Interleukin-8 and lower severity of depression in females, but not males, with treatment-resistant depression. (August 2021) - Kruse, Jennifer L.; Olmstead, Richard; Hellemann, Gerhard; Breen, Elizabeth C.; Tye, Susannah J.; Brooks, John O.; Wade, Benjamin; Congdon, Eliza; Espinoza, Randall; Narr, Katherine L.; Irwin, Michael R.
Abstract: Introduction: In cross-sectional studies of depressed patients, relationships between depression and levels of IL-8 are inconsistent, and have not been examined in relation to sex. Given identified sex differences in longitudinal data, it is important to evaluate sex-specific cross-sectional relationships between IL-8 and depressive symptoms, which may explain some inconsistency in the extant literature. It is further unknown whether IL-8 levels may relate to specific symptom profiles among depressed patients, with or without regard to sex. Methods: Among 108 patients with treatment resistant depression (50 females), we evaluated cross-sectional relationships between IL-8 and depression severity, as measured by the Hamilton Depression Rating Scale [HAM-D] Score, and examined sex-specific relationships, as well as relationships with depressive symptom profiles. Other inflammatory markers (IL-6, IL-10, TNF-α, CRP) were also explored in relation to HAM-D. Results: Higher IL-8 was associated with lower total HAM-D score (standardized β = −0.19, p = 0.049). Sex-specific effects were identified (IL-8 x sex interaction: p = 0.03), in which higher IL-8 related to lower HAM-D score in females (standardized β = −0.41, p = 0.004, effect size (sr 2 ) = 0.17), but not males (standardized β = 0.02, p = 0.91). Among a subset of 94 patients (41 females) who had individual HAM-D items available, we evaluated relationships between IL-8 and HAM-D factor subscores. Across sexes, higher IL-8 was associated with lower anxiety/hypochondriasis subscores (standardized β = −0.31, p = 0.002; sex interaction: p = 0.99). Sex differences were identified for relationships between IL-8 and two other HAM-D factor subscores. Conclusions: IL-8 may be related to anxiety symptoms across sexes, but may have a sex-specific relationship with other depressive symptoms. Further evaluation of sex-specific relationships between IL-8, depression symptom profiles, treatment response, and potential neurobiological correlates, may inform mechanisms of depression pathophysiology and aid in development of precision medicine strategies. Highlights: Among depressed females, but not males, higher IL-8 was associated with lower depression score. Across sexes, higher IL-8 was associated with lower anxiety/hypochondriasis factor scores. Plasma levels of other inflammatory markers (IL-6, IL-10, TNF-α, CRP) were not related to depression score.